2023
DOI: 10.1037/emo0001155
|View full text |Cite
|
Sign up to set email alerts
|

Emotion dynamics among preadolescents getting to know each other: Dyadic associations with shyness.

Abstract: The way children express and respond to emotions when they first meet is crucial to friendship initiation. But for highly shy children, these exchanges are particularly challenging. Existing research is based on individual and total frequency measures of emotion that do not reflect the transactional and dynamic nature of emotions in real-life peer interactions. We examined how shyness and dyadic similarity in shyness influence children’s moment-to-moment dyadic emotion sequences with a new peer. Thirty age- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Previous work has found that shy children are less likely to initiate conversations with others, tend to speak less in conversations, and show a longer latency to spontaneously speak across social contexts (e.g., Asendorpf & Meier, 1993;MacGowan & Schmidt, 2021a;Schmidt et al, 1997Schmidt et al, , 1999. Social fear can be observed in facial expressions, such as a furrowed brow, gaze aversion, and negative or restricted affect (e.g., Colonnesi et al, 2014;Poole & Schmidt, 2022;Sosa-Hernandez et al, 2023). Fearful responses may also be expressed in body posture.…”
Section: Behavioral and Cognitive/affective Manifestations Of Fear In...mentioning
confidence: 99%
“…Previous work has found that shy children are less likely to initiate conversations with others, tend to speak less in conversations, and show a longer latency to spontaneously speak across social contexts (e.g., Asendorpf & Meier, 1993;MacGowan & Schmidt, 2021a;Schmidt et al, 1997Schmidt et al, , 1999. Social fear can be observed in facial expressions, such as a furrowed brow, gaze aversion, and negative or restricted affect (e.g., Colonnesi et al, 2014;Poole & Schmidt, 2022;Sosa-Hernandez et al, 2023). Fearful responses may also be expressed in body posture.…”
Section: Behavioral and Cognitive/affective Manifestations Of Fear In...mentioning
confidence: 99%
“…The study had important limitations as well. Our analytic sample (28 parent-adolescent dyads from the Chicagoland area) was similar in size to other dyadic interaction studies with adolescents (Sosa-Hernandez et al, 2022), but only afforded sufficient statistical power (.80) to detect large effects (.48) at an alpha level of .05, not medium or small effects, as determined by a sensitivity analysis. Thus, the absence of evidence should not be taken as evidence of absence in the present sample.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Emotion dynamics have been shown to correlate with overall well-being, mental health, and psychopathology (the scientific study of mental illness or disorders) (Kuppens and Verduyn, 2017;Houben et al, 2015;Silk et al, 2011;Sperry et al, 2020). Further, studying emotion dynamics allows us to better understand emotions, and has been shown to have ties with academic success (Graziano et al, 2007;Phillips et al, 2002), and social interactions (e.g., shyness) in children (Sosa-Hernandez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%